Accuracy of Bankruptcy Predictions of Real Estate Companies in Indonesia Based on the Altman, Springate, Zmijewski, and Grover Models - Jariah, Ainun; Irdiana, Sukma; Lukiana, Ninik (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
Covid 19 pandemic has been able to shake up the Indonesian property market, this has worried investors who intend to invest their capital in these companies. Therefore, investors or the market must have knowledge about predictions of a company's bankruptcy. There are various types of bankruptcy predictions for early detection of a company's financial condition, including Altman, Springate, Zmijewski, and Grover models. The purpose of this research is to validate the Altman, Springate, Zmijewski, and Grover bankruptcy prediction model. Is there a difference between the four prediction models and which one is the best at foretelling bankruptcy for real estate businesses in Indonesia? Based on the existing criteria, the research sample consisted of 31 companies, using Kruskal Wallis analysis techniques to prove differences and manual calculations to determine the level of accuracy and error rate. The data processing results demonstrate that there are verifiable distinctions amongst the four prediction models and the Asymp value. Sig 0.000 is less than 0.05 the Grover model is the most reliable indicator of impending bankruptcy model with a higher accuracy value than the other three predictions, namely 76% and an error rate of 24%.